Turn-Amplitude Analysis as a Diagnostic Test for Myofascial Syndrome in Patients with Chronic Pelvic Pain - Fernando Itza; Daniel Zarza; Jesus Salinas; Fernando Teba; Carmen Ximenez (Pain Research and Management)
BACKGROUND: Myofascial pain syndrome of the pelvic floor (MPSPF) is a common disease in the context of chronic pelvic pain (CPP); however, there is currently no gold-standard test to diagnose it.